Analisis peran penggalangan intelijen dalam pencegahan konflik disharmoni agama dengan budaya lokal - Hari Purwanto (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
This study aims to analyze the role of increasing intelligence in an effort to prevent disharmony between religion and local culture. The concepts used in this research are acculturation, religion, culture, and religion as a cultural system. This research uses qualitative research with a case study approach. Data was collected through interviews, literature study and documentation. The data analysis technique uses Miles and Hubberman analysis techniques combined with Intelligence analysis techniques. The results showed that the failure of cultural acculturation led to the emergence of potential threats to the mindset of society, social, culture, economy, and security in the Yogyakarta area, and resulted in the erosion of Pancasila values, Javanese cultural identity, and nationalism. cultural identity. Strategies to anticipate potential threats can be overcome through the implementation of intelligence gathering to create conducive security and protect national interests. Activities carried out as a form of raising intelligence by the Regional Intelligence Agency (Bindan) are coordinating to make the Doa Bersama Lintas Agama event at Tugu Yogyakarta successful. This is done as a form of encouragement to minimize disharmony of religion and local culture. Besides that, as a persuasive step, dialogue and friendship from intelligence gathering carried out by Bindan.